THE PROGNOSTIC ROLE OF EGFR AND VEGF IN COLORECTAL CANCER RECURRENCE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
To evaluate whether the expression levels of epidermal growth factor receptor (EGFR) and vascular endothelial growth factor (VEGF) can predict recurrence in colorectal cancer patients, thereby aiding personalized treatment strategies.